Wunderkammern and dissemination for children: Knowing and imagining through wonder (Itinera, 2023)
Wunderkammern represent a truly interesting phenomenon not only because of their pe- culiar feature of collecting amazing, even monstrous, items from all over the planet, but especially for the importance given to feelings such as curiosity, wonder and astonish- ment in the process of discovering the world, as a medium to get to knowledge. Wunder- kammern, also known as Cabinets of Curiosities, keep being represented in art and enter- tainment, with particular relevance to their most grotesque aspects; here, the focus is on two depictions coming from non-fiction children’s literature, which has gone through a recent wave of innovation regarding specifically the picturebooks form. The non-fiction picturebooks edited in the last decade appear to have in common a significant illustration and design apparatus, resulting in a strongly creative and aesthetic approach to knowledge: engaging the senses – and therefore inspiring awe and wonder – together with data and information, these non-fiction picturebooks contribute to restore value to art and beauty in the learning process, revealing a sort of relationship with the Wunderkammer paradigm.